Location Based Services with Location Centric Profiles - M.Ferni Ukrit; B. Venkatesh; Swetabh Suman (Institute of Advanced Engineering and Science, 2016)
In the advancing world of technology, Mobile applications are a rapidly growing segment of the global mobile market. Mobile applications are evolving at a meteor pace to give users a rich and fast user experience. Android operating system supports most applications in today’s technical world. It is an open source operating system which highly satisfies the user’s needs. In this paper, the applications that are location based i.e. the applications that make use of the Global Positioning System (GPS) is discussed. It is a space based satellite navigation system which provides details of time and location in all weather conditions anywhere on or near earth. We introduce PROFILER, a framework for constructing location centric profiles (LCPs), aggregates built over the profiles of users that have visited discrete locations. In addition to a venue centric approach, we propose a decentralized solution for computing real time LCP snapshots over the profiles of collocated users. In our System we find the corresponding location using Global Positioning and Service Provider also. This is to change the profile mode automatically and alarm notification enable automatically when you are going to reach corresponding location or Regular Location.